Efeito do treinamento resistido sobre o coeficiente de controle de fluxo (FCC) da cadeia respiratória mitocondrial do músculo gastrocnêmio de ratas ovariectomizadas - Scarlato, Gabriel Carlos Goulart (2020)
Introduction: Menopause is a marked naturalistic process of female aging, resulting from the progressive decrease in the production of the main ovarian sex hormones permanently. The drop in the production of ovarian estrogens has a negative effect on the striated skeletal muscle system, making women more susceptible to developing sarcopenia. In search of knowledge about the phenomena that occur in the post-menopausal period and their mechanisms of action, models of ovarian removal in rats (OVX) are widely used as an experimental model of menopause induction, effectively reproducing the deleterious effects observed in menopause. The number of studies that have investigated the effect on the functioning of the electron transport chain (CTE) and its relationship with ANT-1 gene expression in OVX rats is limited, as well as the effects of resistance training (TR) intervention in this context. Objective: This study aims to evaluate the effects of resistance training on the functioning of protein complexes in the respiratory chain during coupled and uncoupled breathing in the experimental model of ovariectomized rats, as well as the ANT-1 gene expression. Materials and Methods: In this study, 40 adult Wistar rats were randomly assigned to 4 experimental groups: INT-SED, INT-TR, OVX-SED and OVX-TR. Ovariectomy was performed in the 13th week of life of these animals. The RT model performed was the stair climbing, lasting 22 weeks. The body tissues of interest were analyzed after euthanasia, which occurred 48 hours after the last training session. Oxygen consumption (O2) and mitochondrial respiratory parameters were performed on tissue biopsy of the Gastrocnemius muscle using the High Resolution Respirometry technique (Oroboros®). The titrations to establish the Flow Control Coefficient (FCC) were performed at ANT, at the Phosphate Exchanger and at the ATP-Synthase. Results: Ovarietomy negatively affected the functioning efficiency of ANT-1 and ATP synthase in the sedentary group (OVX-SED). Regarding oxygen consumption, in the coupled respiratory state (E3) there was a significant decrease in the consumption of the OVX-SED group compared to the other 3 groups, an effect reversed by the resistance training adopted in the study; both trained groups obtained excellent FCC values and oxygen consumption at E3. Conclusion: We conclude that ovariectomy promotes a decrease in the efficiency of the FCC of ANT and ATP-Synthase of the gastrocnemius muscle of sedentary OVX rats, as well as promoting a decrease in oxygen consumption at E3. An RT program is potentially capable of preventing these harmful responses and maintaining mitochondrial function in physiological conditions.